The Impact of Simulation-Based Trabeculectomy Training on Resident Core Surgical Skill Competency. Issue 1 (22nd January 2023) - Annoh, Roxanne; Buchan, John; Gichuhi, Stephen; Philippin, Heiko; Arunga, Simon; Mukome, Agrippa; Admassu, Fisseha; Lewis, Karinya; Makupa, William; Otiti-Sengeri, Juliet; Kim, Min; MacLeod, David; et al.
Abstract : Précis: Simulation-based surgical education shows a positive, immediate, and sustained impact on core surgical skill competency in trabeculectomy among resident ophthalmologists in training. Purpose: To measure the impact of trabeculectomy, surgical simulation training on core surgical skill competency in resident ophthalmologists. Materials and Methods: This is a post hoc analysis of the GLAucoma Simulated Surgery trial, which is a multicenter, multinational randomized controlled trial. Resident ophthalmologists from 6 training centers in sub-Saharan Africa (in Kenya, Uganda, Tanzania, Zimbabwe, and South Africa) were recruited according to the inclusion criteria of having performed zero surgical trabeculectomies and assisted in <5. Participants were randomly assigned to intervention and control arms using allocation concealment. The intervention was a 1-week intensive trabeculectomy surgical simulation course. Outcome measures were mean surgical competency scores in 8 key trabeculectomy surgical skills (scleral incision, scleral flap, releasable suturing, conjunctival suturing, sclerostomy, tissue handling, fluidity, and speed), using a validated scoring tool. Results: Forty-nine residents were included in the intention-to-treat analysis. Baseline characteristics were balanced between arms. Median baseline surgical competency scores were 2.88/16 [interquartile range (IQR): 1.75–4.17] and 3.25/16 (IQR: 1.83–4.75) in the intervention and control arms, respectively. At primary intervention, median scores increased to 11.67/16 (IQR: 9.58–12.63) and this effect was maintained at 3 months and 1 year ( P =0.0001). Maximum competency scores at primary intervention were achieved in the core trabeculectomy skills of releasable suturing (n=17, 74%), scleral flap formation (n=16, 70%), and scleral incision (n=15, 65%) compared with scores at baseline. Conclusions: This study demonstrates the positive impact of intensive simulation-based surgical education on core trabeculectomy skill development. The rapid and sustained effect of resident skill acquisition pose strong arguments for its formal integration into ophthalmic surgical education.